Unraveling the dyadic dynamics: exploring the impact of flexible working arrangements’ availability on satisfaction with work-life flexibility among working parents - Ya Guo; Fenwick Feng Jing; Yuqi Zhong; Meng Zhu; Senhu Wang (Humanities & Social Sciences Communications)
Abstract Despite ample research on the association between the availability of flexible working arrangements (FWAs) and satisfaction from an individual perspective, little has explored the dyadic correlation between the availability of FWAs and satisfaction with work-life flexibility (WLF) from a couple-level perspective among working parents. Drawing on a linked lives perspective and the work-family border theory, this study contributes to the literature by adopting the longitudinal couple-level dyadic data from the Household, Income, and Labour Dynamics in Australia (HILDA) survey (2001–2021) to examine how couples’ availability of FWAs affects their own and their spouses’ satisfaction with WLF among working parents. The results show that among couples with children, mothers’ availability of FWAs significantly improves their own and their husbands’ satisfaction with WLF. In contrast, fathers’ access to FWAs only improves their own satisfaction with WLF. Moreover, the impact of one’s availability of FWAs on their satisfaction with WLF, as well as the effects of mothers’ availability of FWAs on their husbands’ satisfaction, are more pronounced among formal contract workers. Overall, this study underscores the dyadic association between couples’ FWAs and satisfaction with WLF among working parents, delineating an asymmetric dynamic.